KREATIVITAS GURU PAI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - Ensi; Imam Syafi’i; Endang Ekowati (UNISAN JURNAL, 2023)
Based on the research focus, the authors formulated the problem in this study as follows: How is the creativity of PAI teachers in increasing the motivation and learning outcomes of students in PAI subjects at SDIT Ishlahul Ummah Prabumulih in the 2022/2023? Academic year and what are the supporting and inhibiting factors? Considering that in this study, the authors wanted to see what teacher creativity was in increasing the motivation and learning outcomes of students in PAI subjects, this research was descriptive in nature. Data collection techniques in this study used several methods, namely: (1) observation method, (2) interview method and (3) documentation method. Based on the discussion of the previous chapter, the writer can draw the following conclusions: The learning outcomes of students with the creativity of PAI teachers have increased based on learning outcomes in cognitive, student affective and psychomotor aspects contained in report cards and besides supporting factors, there are also other factors the obstacles in increasing the creativity of PAI teachers in increasing the motivation and learning outcomes of students in PAI subjects at SDIT Ishlahul Ummah Prabumulih which the authors identify include internal factors and external factors